Reading and writing in university teacher training: strategies for comprehension, written expression and the responsible use of technology - Bort Caballero, María Luz; Bort-Caballero, María de la Luz (Centro de Investigación en Educación, Naturaleza, Cultura e Innovación para la Amazonia, 2026)
Introduction: Spain’s current university education context has experienced a worrying decline in deep reading and writing practices, displaced by digital consumption habits and characterized by immediacy, superficiality, and intensive use of artificial intelligence tools. Methodology: This paper analyzes this phenomenon from a qualitative and reflective pedagogical perspective and proposes a didactic intervention aimed at the initial training of early childhood and primary school teachers. Results: It also presents a work proposal structured in three integrated phases under the Project-Based Learning (PBL) approach and the use of digital storytelling. First, an individual process of reading comprehension and written expression is developed based on the analysis of texts related to the life and work of a woman author. Second, students collaborate in teams to create digital narratives focused on her biography and adapt one of her works for children readers, thus strengthening creativity, cooperation, and communication skills. Finally, an adaptation phase is incorporated to address diversity, integrating the responsible use of artificial intelligence tools for educational and accessibility purposes. This project promotes the development of reading, writing, and critical skills, while consciously integrating the potential of educational technology. Conclusions: Grounded in practice- informed pedagogical inquiry, it proposes a methodological alternative to strengthen the link between reading, writing, inclusion, and technology, preparing future teachers to address the challenges of teaching in the digital age with responsibility and creativity.
La lectura y la escritura en la formación universitaria de maestros y maestras: estrategias para la comprensión, la expresión escrita y el uso responsable de la tecnología
Keywords: Investigación activa en educación; Profesores - Formación profesional; Escritura - Estudio y enseñanza superior; Reading; Writing; Teacher training; Written expression; Written comprehension; Technology